RANCANG BANGUN APLIKASI CLOUD STORAGE DENGAN ANGGULAR DAN FIREBASE BERBASIS ANDROID - Fathurrahman Kurniawan Ikhsan; Fatimah Fahurian; Aliy Hafiz (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2019)
Cloud storage is a development of cloud-based data storage, then Firebase provides services, one of which is Firebase storage, which is one of the technologies in the field. Cloud storage technology allows Android users to store data without requiring physical storage, specifically for Android users themselves the use of cloud storage will be very useful as an alternative storage media or backup media so that data is not easily lost. The design of cloud storage applications using Android-based firebase was developed beginning with analyzing needs, designing the appearance of applications, building applications, inputting program code, and testing applications. Output results to be achieved are the generation of cloud storage applications that can store various types of file extensions, are easy to use, and can run well on the Android platform. From this research, the results are obtained: first Cloud Storage technology is very useful as a data storage medium so that data is not easily lost, secondly making an Android application with Angular can be built with Cordova to run on the Android platform, thirdly Firebase has many features and services that can be used in the development of android applications, one of which is firebase storage.